Effects of eye health among youngster while playing computer game - Nurul Saidatul Akmal, Ab. Razak; Rahmah, Mokhtar (IEEE, 2021)
Computer games have become popular among youngsters for entertainment and education nowadays. Due to this situation, the youngster faces a problem that can lead to eye health problems such as eye fatigue, eye strain, redness of the eye and dry eye. This paper aims to find relation ship between eye blinking and eye health for the youngsters while playing computer games. A survey has been done on 232 parents to find out their worriedness about their youngster's eye health. The result shows that 99% of parents worry about their youngster's eye health and 89% agree that prolong computer usage can lead to eye health issues. Also, an experiment on ten youngsters has been done based on eye blinking to find relationship between eye blinking and eye health. Experiments show a 95% confidence interval, indicating a relationship between eye blinking and eye health, where less eye blinking can harm the eye. Therefore, the guideline of games should be implemented in the future.